2020
DOI: 10.11609/jott.5730.12.10.16314-16346
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of macrofungi (mushroom) diversity and distribution in the forests of Tripura, India

Abstract: The tropical region, which has the highest macrofungi diversity, has not been fully exploited instead of this is an important component of the global diversity. However, no work has been carried out to assess such diversity in Tripura. Since tropical forests are diverse in plant composition and structure, hence the objective of this study was to explore the mushroom species richness in Tripura, Northeast India with the aim of producing a checklist along with their present geographical distributions, key identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…These findings were in line with the results of our study were in we documented highest number of species belonging to order Pezizales. The findings of our study agreed with the studies of Debnath et al (2020) who prepared a checklist of macrofungi from the forests of Tripura, India where in authors reported and documented 217 species with majority of Basidiomycetes, followed by a smaller number of Ascomycetes mushrooms. In a similar studies Tapwal et al (2013) and Singha et al (2017) reported 30 and 71 species of macrofungi from different several regions of India.…”
Section: Due To Conducive Climatic Conditions In Kashmirsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings were in line with the results of our study were in we documented highest number of species belonging to order Pezizales. The findings of our study agreed with the studies of Debnath et al (2020) who prepared a checklist of macrofungi from the forests of Tripura, India where in authors reported and documented 217 species with majority of Basidiomycetes, followed by a smaller number of Ascomycetes mushrooms. In a similar studies Tapwal et al (2013) and Singha et al (2017) reported 30 and 71 species of macrofungi from different several regions of India.…”
Section: Due To Conducive Climatic Conditions In Kashmirsupporting
confidence: 92%
“…Rainfall and the availability of decomposed organic waste are two examples of natural elements that have an impact on the distribution and abundance of wild macrofungi (Swapna et al 2008;Debnath et al 2017). The presence of mushrooms in plantation sites and forest beds indicates a direct relationship between the mushroom population and the physical health of the forest (Debnath et al 2017). During the current research maximium number of Ascomycetous mushrooms were recorded in rainy seasons which helps in decomposition of dead organic matter.…”
Section: Due To Conducive Climatic Conditions In Kashmirmentioning
confidence: 67%
See 1 more Smart Citation
“…They are widespread in nature and are a permanent component of biogeocenoses [17,18]. As heterotrophic organisms, they take an active part in the biological cycle of substances and energy [19,20] Currently, the main commonly accepted characteristics of biodiversity are species composition, taxonomic structure and spatial organization.…”
Section: Introductionmentioning
confidence: 99%
“…Such mushrooms flourish the forest floor well in the rainy season. Mushrooms are fleshy, spore bearing fruiting body of a fungus and are the major biological constituent in forest ecosystem [5]. From the ancient time wild mushrooms have been fulfilling the need of food and nutraceutical among the aboriginals.…”
Section: Introductionmentioning
confidence: 99%